Negotiation Strategy and Professionalism of Master of Ceremonies in the Wedding Industry in Indonesia - Nur Rohman, Haris Nuzul; Harmonis, Harmonis (COMMUSTY Journal of Communication Studies and Society, 2024)
This research project aims to analyse the negotiation strategies employed by professional Master of Ceremonies (MCs) in the wedding industry in Indonesia. The study focuses on how MCs manage communication, build a professional image, and utilise social media and professional communities as part of their negotiation strategies. A qualitative approach was employed to collect data through in-depth interviews and participatory observation with three well-known MCs. The findings indicate that effective negotiation strategies in this context entail the utilization of framing techniques, flexible strategizing and the management of interpersonal relationships in a proficient manner. Furthermore, the study demonstrated that the professionalism of an MC is contingent upon not only their technical proficiency in event hosting, but also their capacity to cultivate and sustain a professional image through social media and active involvement in professional communities such as the Indonesian Wedding Host Association (HIPAPI). These MCs were able to enhance their negotiating position by showcasing an extensive portfolio of work on social media and developing a reputation through professional networks. This strategy not only augmented their credibility in the eyes of the client, but also facilitated the negotiation process by establishing robust initial trust. The findings substantiate that a combination of effective communication strategies, utilization of social media, and engagement in professional communities are pivotal to achieving mutually beneficial agreements in the Indonesian wedding industry.